Analysis of the Anxiety Level Among the Players of Serpong City FC In Facing the 2023/2024 Indonesian Liga 3 Competition - Fathan Nur Ramadhan; Muhammad Arief Setiawan; Dany Aulia (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2023)
The sport of football is a branch of sports that has gained a lot of enthusiasts and competitors aiming to become high-achieving players. Therefore, players must train their mental resilience from an early age in order to be able to manage anxiety when facing a competition. This study falls under the category of a survey with a quantitative descriptive approach, using a questionnaire as the data collection tool. The focus of this research is to investigate the anxiety levels of players before facing the competition in the 2023/2024 Liga 3. There were 22 players selected as samples for this study. The instrument used for data collection was a questionnaire designed to measure the players' anxiety levels, utilizing the Sports Competition Anxiety Test (SCAT) as a sports anxiety instrument. The implementation phase involved providing instructions to the sample regarding the process of filling out the questionnaire regarding the profile of anxiety levels in players, and then collecting the data by distributing the questionnaire to the players. The results of this study showed that the anxiety levels of the Serpong City FC players for the 2023/2024 season before competing in the Liga 3 Indonesia 2023/2024 were as follows: 7 respondents (32%) experienced low anxiety levels with an average score of 15.14, 10 respondents (50%) experienced moderate anxiety levels with an average score of 19.5, and 5 respondents (22%) experienced high anxiety levels with an average score of 25.4. This provides insight to the coach and officials that they should focus on training the mental resilience of the players and help find solutions to the anxiety issues experienced by the Serpong City FC players, especially those participating in the Liga 3 competition for the first time. It also raises the question of whether the anxiety is intrinsic or extrinsic. Based on the results obtained, it can be interpreted that the anxiety levels of the Serpong City FC players for the 2023/2024 season fall into the moderate category, with an average score of 18.9.